A review of the genus Scaphidium Oliver (Coleoptera, Staphylinidae, Scaphidiinae) from Tianmushan, East China - He, Wen-Jia; Tang, Liang; Li, Li-Zhen (Zootaxa, 2008)
Five species of the genus Scaphidium are recorded from the Tianmushan mountain chain, including Scaphidum wuyongxiangi He, Tang & Li, sp. nov. The male of S. stigmatinotum Löbl is discovered and described for the first time. The variability of S. sinense Pic is discussed. A key to Scaphidium species of this area is provided.